Pola Asuh Karyawati Rokok Muslimah dalam Membina Karakter Anak Usia Dini di Kabupaten Sumenep Madura Indonesia - Muru'atul Afifah; Ulfatul Hasanah (KURAS Institute, 2022)
Nowadays, the number of female workers in various companies is commonplace. As a result, women's parenting pattern is not intensive. In Islamic teachings, women have a great responsibility in educating children. This paper aims to look at the phenomenon of child rearing by Muslimah cigarette employees in Bulu Lebilleh Hamlet, Pragaan Daya Village, Sumenep, Madura. This paper uses a qualitative field method with a phenomenological approach. Data collection is done by interview, observation, and documentation. The results showed that five Muslimah cigarette employees entrusted their children to their families (husbands and parents) when they worked. The parenting style of Muslimah employees is limited. Among them are teaching their children to be independent, such as eating and bathing themselves, teaching the recitation of the Qur'an, teaching them to read prayers, and teaching children to color and draw. The supporting factors for the success of Muslimah cigarette employees in fostering the character of early childhood are a conducive environment and a harmonious family. The inhibiting factors are the limited time and defiance of children due to parenting patterns that are not optimal